2011
DOI: 10.1007/s10499-011-9460-x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and gonad development of the tropical black-lip pearl oyster, Pinctada margaritifera (L.), in the Gambier archipelago (French Polynesia)

Abstract: The growth and reproductive cycle of cultured black-lipped pearl oysters, Pinctada margaritifera (L.), were studied in the Gambier Islands (134°52 0 W, 23°07 0 S) from September 2002 to August 2003. Temperatures were recorded throughout the year, revealing seasonal temperature variations between 22.3 and 27.8°C. The mean annual chlorophyll a value, as computed from satellite data, was 0.188 ± 0.075 lg L -1 . To study growth and reproduction, 720 two-year-old individuals were ear hung on long-lines suspended at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…In tropical area such as French Polynesia, however, there is no clear seasonal cycle because there is little temperature variations. Pearl oysters are reproductively active almost all year round (Pouvreau et al, ; Le Moullac et al, ), with abundant trophic resources promoting gametogenesis and spawning (Fournier et al, ). A recent study in P. margaritifera confirmed that gametogenesis is modulated by food level: under‐feeding decreases or stops germinal activity preventing any resumption of gametogenesis (Le Moullac et al, ).…”
mentioning
confidence: 99%
“…In tropical area such as French Polynesia, however, there is no clear seasonal cycle because there is little temperature variations. Pearl oysters are reproductively active almost all year round (Pouvreau et al, ; Le Moullac et al, ), with abundant trophic resources promoting gametogenesis and spawning (Fournier et al, ). A recent study in P. margaritifera confirmed that gametogenesis is modulated by food level: under‐feeding decreases or stops germinal activity preventing any resumption of gametogenesis (Le Moullac et al, ).…”
mentioning
confidence: 99%
“…Studies of females and males have been made on Icelandic scallop Chlamys islandica (Vahl and Sundet 1985), freshwater eastern floater mussel Pyganodon cataracta (Tankersley and Dimock 1993), Sydney rock oyster Saccostrea glomerata (Honkoop 2003), and Pacific oyster Crassostrea gigas (Soletchnik et al 1997;Tran et al 2008). In our study, apart from a wide range of factors acting on metabolic functioning of P. margaritifera (Yukihira et al 1998(Yukihira et al , 2000Pouvreau et al 1999Pouvreau et al , 2000Le Moullac et al 2012), we focused on specific metabolic responses of females and males. This provided the first information concerning specific metabolic behaviours related to gender in this species.…”
Section: Discussionmentioning
confidence: 99%
“…The oysters were laid out in a collector, where their waste was retained on a 10 µm sieve. The waste was analysed according to Le Moullac et al (2012).…”
Section: Experimental Designmentioning
confidence: 99%
“…For sounding physiological changes of sexual development of this animal, we draw these changes through visual and microscopic inspection of smears from the fresh sexual glands of females and males, that was followed by many researchers (Lucas and Beninger, 1985;Guillou et al, 1990;Pouvreau, 1999;Kimani and Mavuti, 2002;Kimani et al, 2006;Le Moullac et al, 2012), which gave us a dependable result in the preliminary determination and reading of the nature of sexual reproductive cycle of this important mollusk for the first time in Hadhramout coast environment.…”
Section: Study Areamentioning
confidence: 99%
“…Frequency distribution of relative size of males, females, and juvenile pearl oysters (Pinctada margaritifera) identified by gonadal smears examination of specimens, in Hadhramout coast Moullac et al (2012). that P. margaritifera could be defined as an opportunistic spawner.…”
mentioning
confidence: 99%